Late Permian palaeoenvironmental evolution of the Matinde Formation in the Muaradzi Sub-basin, Moatize-Minjova Basin, Mozambique - Lopes, Gilda (2021)
A multidisciplinary study involving lithofacies analysis, palynofacies, and palynology is presented for the Muaradzi Sub-basin. This sub-basin is part of the Moatize-Minjova Basin (MMB), an important Karoo aged coalfield in Mozambique. A total of 99 core samples from 3 coal exploration boreholes (DW11, DW21, and DW141) were analysed and all the successions were assigned a Lopingian age based on palynology. According to the data, in the Muar ' adzi Sub-basin, a vast lowland fluvial setting existed with floodplains and wetlands, in an area controlled by tectonic movements associated with a continental rifting phase. Typical vegetation of the Glossopteris Province is recorded in the palynological assemblages of this sub-basin, which allowed for the characterization of a flora dominated by glossopterids (Protohaploxypinus and Striatopodocarpites) and gymnosperm pollen (Alisporites). Other palynomorphs revealed the presence of gingkoales, ferns (Filicopsida), sphenopsids, and lycopsids in the area, indicating a typical lowland setting. Humid and warm climates, associated with higher CO2 atmospheric levels, promoted the growth of widespread vegetation that led to the development of the thick coal beds in anoxic to dysoxic depositional environments.